Media as medium in colombian education: how media and ICT are changing communication and the curriculum in the school - Rodríguez Bohórquez, Carolina; Hine, Nicolas (Colombian Applied Linguistics Journal, 2009)
We describe how secondary school students are engaged in designing school newspapers, broadcasting radio shows and using ICT in classrooms as opportunities for communication and learning. The central goal in this project was to set up the school dynamics where radio, newspaper, television, video, images and ICT´s play the role of additional inputs and increase the community interest in literacy. We present some practical initiatives that demonstrate the possibilities of media literacy based activities in a public school in Bogota, Colombia